PHYSIOTHERAPEUTIC REHABILITATION IN THE POSTOPERATIVE PERIOD OF TOTAL HIP ARTHRECTOMY (REMUNOM, 2025)
Total hip arthroplasty (THA) is a surgical procedure widely indicated in cases of degenerative or traumatic diseases of the hip joint, with the aim of relieving pain, restoring joint function, and improving the patient's quality of life. This study aimed to evaluate the physiotherapeutic evolution of a patient in the postoperative phase of total hip arthroplasty, treated at the Teaching and Research Clinic in Physiotherapy of Iguaçu University (UNIG). This is a case study conducted with a 47-year-old male patient who underwent uncemented/hybrid total hip arthroplasty. The physiotherapeutic evaluation included a detailed anamnesis, physical examination, joint and muscle strength tests, perimetry, measurement, and sensitivity assessment. The physiotherapeutic treatment consisted of laser therapy, myofascial release, therapeutic stretching, kinesiotherapy, joint mobilization, and scar mobilization, progressing to gait training and dynamic balance. After treatment, significant improvements were observed in muscle strength, range of motion, gait, and stability, in addition to a reduction in edema and pain. It is concluded that individualized physiotherapy intervention presented positive results in the postoperative rehabilitation of total hip arthroplasty, favoring functional return, independence, and quality of life for the patient.